Design and clinical application of injectable hydrogels for musculoskeletal therapy - Ovrebo,O; Perale,G; Wojciechowski,J; Echalier,C; Jeffers,J; Stevens,M; Haugen,H; Rossi,F (Bioengineering and Translational Medicine, 2022)
Musculoskeletal defects are an enormous healthcare burden and source of pain and disability for individuals. With an ageing population, the proportion living with these medical indications will increase. Simultaneously, there is pressure on healthcare providers to source efficient solutions, which are cheaper and less invasive than conventional technology. This has led to an increased research focus on hydrogels as highly biocompatible biomaterials that can be delivered through minimally invasive procedures. This review will discuss how hydrogels can be designed for clinical translation, particularly in the context of the new European Medical Device Regulation (MDR). We will then do a deep dive into the clinically used hydrogel solutions that have been commercially approved or have undergone clinical trials in Europe or the US. We will discuss the therapeutic mechanism and limitations of these products. Due to the vast application areas of hydrogels, this work focuses only on treatments of cartilage, bone, and the nucleus pulposus. Lastly, the main steps towards clinical translation of hydrogels as medical devices are outlined. We suggest a framework for how academics can assist small and medium MedTech enterprises conducting the initial clinical investigation and Post-Market Clinical Follow-up (PMCF) required in the MDR. It is evident that the successful translation of hydrogels is governed by acquiring high-quality pre-clinical and clinical data confirming the device mechanism of action and safety.